The Relationship Between Parental Attention and the use Of Audio-Visual Media Online Learning with Economic Learning Outcomes at Muhammadiyah 1 Palangkaraya High School - Yolandari, Leni; Estimurti, Endang Sri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: class used by parents for work, also during the online learning process using audio-visual media in economics subjects, many students are less enthusiastic in carrying out the teaching and learning process, many students do not pay attention and rarely ask questions when after the teacher explains they also ask students cannot answer and just keep quiet. Aim: This study aims to determine the relationship between parental attention and the use of audio-visual media for online learning and economic learning outcomes at Muhammadiyah 1 Palangkaraya High School. Method: The research method used is quantitative methodology. The population in this study are students of classes X Natural science 1, X Social science 1, and X Social science 2 at Muhammadiyah 1 Palangkaraya High School, which is as many as 69 students. And data collection techniques using questionnaire and test and analysis techniques using product moment correlation and multiple correlation. Results and Dıscussion: From the results of the study, it can be concluded that: (1) There is a positive relationship between the attention of parents of students and economic learning outcomes in class X at Muhammadiyah 1 Palangkaraya High School in 2022/2023 with a correlation coefficient Γx1y = 0.665. This relationship includes a strong relationship, (2) There is a positive relationship between the use of audio-visual media for online learning by students and the learning outcomes of class X economics at Muhammadiyah 1 Palangkaraya High School in 2022/2023, with a correlation coefficient of Γx1y = 0.574. The relationship includes a moderate relationship, (3) There is a relationship between parental attention and the use of audio-visual media and the learning outcomes of grade X economics at Muhammadiyah 1 Palangkaraya High School in 2022/2023, with a correlation coefficient of Γx1y = 0.685. The relationship includes a strong relationship.